GLP-1 receptor agonists: a review of head-to-head clinical studies. (February 2015) - Trujillo, Jennifer M.; Nuffer, Wesley; Ellis, Samuel L.
Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are attractive options for the treatment of type 2 diabetes (T2D) because they effectively lower A1C and weight while having a low risk of hypoglycemia. The GLP-1 RA class has grown in the last decade with several agents available for use in the US and Europe and several more in development. Since the efficacy and tolerability, dosing frequency, administration requirements, and cost may vary between agents within the class, each agent may offer unique advantages and disadvantages. Through a review of phase III clinical programs for exenatide twice daily, exenatide once weekly, liraglutide, albiglutide, lixisenatide, and dulaglutide, eight head-to-head trials have evaluated the safety and efficacy of GLP-1 RA active comparators. The purpose of this review is to provide an analysis of these trials. The GLP-1 RA head-to-head clinical studies have demonstrated that all GLP-1 RA agents are effective therapeutic options at reducing A1C. However, differences exist in terms of magnitude of effect on A1C and weight as well as frequency and severity of adverse effects.